Real-world opioid prescribing after cataract surgery among patients who received intracameral phenylephrine and ketorolac 1.0%/0.3%. (1st December 2020) - Jackson, Kevin; Wisely, C. Ellis; Davis, Brian M.; Griffin, Brian; Kim, Terry
Abstract: Objective: To examine opioid prescribing following cataract surgery among patients who did or did not receive Omidria (phenylephrine and ketorolac intraocular solution 1.0%/0.3%) referred to as "P/K". Methods: The retrospective study compared adults over 65 without recent opioid use in the MarketScan databases who had a cataract-related surgical procedure between 1 January 2015 and 31 July 2019. Opioid prescription fills in the initial 2 and 7 days following surgery were compared between patients who did or did not receive P/K during surgery. Results: We identified 218, 672 older adults with cataract-related surgical procedures, of whom 5145 received P/K during surgery. Within 2 days of surgery, 0.50% of P/K patients and 0.68% of non-P/K patients received at least one opioid prescription. Pill counts in the first prescription post-surgery were lower for patients who received P/K than those who did not receive P/K (20 vs 45 respectively, p  = .015). Findings were similar when a 7 day window was used. The reduction in opioids prescribed to patients who received P/K occurred despite the P/K-treated patients having a significantly higher incidence of preoperative comorbidities or risk factors for surgical complexity than patients who did not receive P/K (46.6% vs 31.3%, p  < .001). Conclusions: Patients without recent opioid use who received P/K during cataract surgery, despite greater incidence of preoperative comorbidities and higher risk for surgical complexity, were prescribed fewer opioid pills following surgery than patients who did not receive P/K.